Puppets for Blessings: Enhancing the Skills of Educators and Children's Ministry Workers Through Puppet - Tiladuru, Vena Melinda; Nenny Natalina Simamora; Desmiyati Rambu Loda; Alvionita Rambu Ngguna (Society : Jurnal Pengabdian Masyarakat, 2026)
This community service program titled "Boneka untuk Berkat" aimed to improve the teaching skills of Sunday school teachers and children’s ministry workers through puppet stage training. The background of the program addresses the lack of creative teaching methods and inadequate training among child educators, which hampers the effective communication of biblical messages. Puppet theatre was introduced as a creative, interactive, and age-appropriate media to communicate God’s Word to children. The method involved three main stages: (1) Theological foundation and principles of puppet ministry, (2) Practical session on creating hand puppets using simple materials, and (3) Simulation and stage performance guided by a puppet ministry team. The training was conducted on April 1, 2025, at STT SAPPI Cianjur, attended by 92 participants including Sunday school teachers, kindergarten teachers, and theology students. Evaluation results from 50 respondents indicated that 60% found the materials highly relevant, 54% said the goals were fully achieved, and 62% felt highly enthusiastic. The training proved successful in equipping participants with practical skills in puppet performance and script creation, enhancing their capacity to deliver biblical messages in an engaging manner. This initiative contributes to the integration of performing arts with Christian education and demonstrates the value of experiential learning in ministry contexts. Further development of curriculum-based modules and exploration of digital puppet shows are recommended for broader and sustained implementation.